Current Approaches to Ambient Assisted Living - Röcker, Carsten; Ziefle, Martina (2012 International Conference on Future Information Technology and Management Science & Engineering ; Lectute notes in information technology : (LNIT))
Research in the field of technology-supported personal care gained considerable momentum over the last 10 to 15 years. This paper provides a comprehensive overview over state-of-the-art research activities in this field by illustrating major projects and research initiatives as well as highlighting successful approaches to Ambient Assisted Living.
Keywords: Smart medical services; ambient assisted living; E-healt; intelligent environments; ubiquitous and pervasive computing